Polish Library of Studies about crucial Films - Mareš, Petr (Iluminace, 2006)
Reviews of several Polish publications dealing directly with specific films. These are, for example, films: Persona (I. Bergman), Knife in the Water (R. Polanski), etc.
Keywords: film literature